Pemetaan Sumber Daya Laut Pulau Nias dengan Teknologi Penginderaan Jauh Satelit Pasca-Tsunami 2004 - Jonson Lumban Gaol; Risti Endriani Arhatin; Djisman Manurung; Mujizat Kawaru (Institut Pertanian Bogor, 2007)
Accurate and up-to-date information of marine resources is needed for optimum resource utilization. If the required information cannot be obtained with traditional field surveys, remote sensing as a tool for providing fast, efficient, and accurate information is used to detect the changes. The study aims to use remote sensing data for assessing distribustion and condition of marine resources in Nias water's before and after tsunami. Marine resources pararameter derived remote sensing data are sea surface temperature (SST), suspended solid matter, chlorphyll-a concentration, coral reef and mangrove distributions. Mapping and differences in coral reef and mangrove distribution were evaluated using two scans of Landsat image in 1989 and 2005. Sea surface temperature was derived from NOAA-AVHRR data, and chlorophyll-a concentration was derived from SeaWiFS data. The study showed that there were no significant changes of coral reef and mangrove distribution, SST, chlorophyll-a concentration after and before tsunami. Spectral analysis of SST and chlorophyll-a showed that the variability of the parameters was affected by monsoon system and global climate change, namely El Nino Southern Oscillation and Indian Ocean Dipole.Keywords: remote sensing, satellite, Nias, tsunami, chorophyll-a, coral reef, mangrove